1997
DOI: 10.1002/(sici)1096-9071(199704)51:4<259::aid-jmv1>3.3.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Human herpesvirus‐6 reactivation in a longitudinal study of two HIV‐1 infected patients

Abstract: After primary infection, human herpesvirus-6 (HHV-6) persists in latent form and can be reactivated in immunocompromised subjects. A longitudinal study of HHV-6 infection was carried out in two HIV-1 seropositive patients to provide in vivo evidence of HHV-6 reactivation. Concomitant with a significant rise of anti-HHV-6 IgG detected by IFA, a transient increase of HHV-6 viral load was shown in PBLs by PCR. During HHV-6 reactivation it was also identified either cell-free HHV-6 by PCR in plasma or IgM antibody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…A limitation was that anti-HHV6 IgG and anti-EBV EBNA and VCA IgG were only measured at baseline, but these antibodies are relatively stable over time. 36,37 Our analysis found that the association persisted when we restricted the analysis period to 1 year and 6 months post anti-human herpesvirus IgG measurement, providing support that the observed finding reflects a true effect, rather than a statistical artifact.…”
Section: Strengths and Weaknessessupporting
confidence: 59%
“…A limitation was that anti-HHV6 IgG and anti-EBV EBNA and VCA IgG were only measured at baseline, but these antibodies are relatively stable over time. 36,37 Our analysis found that the association persisted when we restricted the analysis period to 1 year and 6 months post anti-human herpesvirus IgG measurement, providing support that the observed finding reflects a true effect, rather than a statistical artifact.…”
Section: Strengths and Weaknessessupporting
confidence: 59%
“…Contrasting with these findings, our investigation has shown HHV-6A variant to be associated with apparently immunocompetent individuals. Of note, it has been reported that immunocompromised and immunocompetent subjects are usually associated with reactivation 28,29 and primary infections 32,45,54 , respectively, whatever variant considered. Of note, latency and later reactivation are both biological properties attributable to HHV-6A and HHV-6B variants in cells and body tissues 6,7,20,38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…HHV-6 strain characterization by PCR demonstrated that the first patient (a woman with 232 CD4+ cell/mm 3 at the beginning, 34 CD4+/mm 3 with full-blown AIDS 16 months later) initially carried the B variant followed by reactivation and persistence of the A variant, while in the second patient (a man with 248 CD4+ at the beginning, then 14 CD4+/mm 3 , Pneumocystis carinii pneumonia and esophageal candidiasis 13 months later) only the A variant was detected. The evidence of HHV-6A reactivation presented suggests its involvement in a mechanism of immunologic damage underlying the disease by either direct destruction of lymphoid cells or altering cytokine pattern (Iuliano et al, 1997). In another longitudinal follow-up of two AIDS patients from active HHV-6A infection evidence was demonstrated but the profile of infection in the two patients varied.…”
Section: Longitudinal Serological and Molecular Studiesmentioning
confidence: 90%